2009
DOI: 10.1007/s10549-009-0617-5
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 promotes cell survival and is predictive of a poor outcome in ERα-negative breast cancer

Abstract: Gli1 is a transcription factor and oncogene with documented roles in the progression of several cancer types, including cancers of the skin and pancreas. The contribution of Gli1 to the progression of breast cancer is less established. In order to investigate the functional impact of Gli1 in breast cancer, expression of Gli1 and its contribution to cell growth was assessed in breast cancer cell lines. These in vitro results were compared to expression of Gli1, determined by immunohistochemistry, in 171 breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…The high expression level of GLI1, the key downstream effector of the Hedgehog signaling pathway, is associated with unfavorable overall survival in cancer patients [48], [49]. Moreover, a recent study demonstrated that GLI1 was a central regulator of cancer stem cells in triple-negative breast cancer [50].…”
Section: Discussionmentioning
confidence: 99%
“…The high expression level of GLI1, the key downstream effector of the Hedgehog signaling pathway, is associated with unfavorable overall survival in cancer patients [48], [49]. Moreover, a recent study demonstrated that GLI1 was a central regulator of cancer stem cells in triple-negative breast cancer [50].…”
Section: Discussionmentioning
confidence: 99%
“…PTCH protein expression showed a positive correlation with ER positive, but not PR positive breast cancers [81]. Gli1 (nuclear GLI1 protein) and ERα mRNA and protein expression correlate in many patient tumors and breast cancer cell lines [86,98100]. Estradiol treatment can induce GLI1 mRNA, and nuclear localization of GLI1 in ER positive breast cancer cell lines to promote proliferation, survival, and invasiveness [86,98,100].…”
Section: Hedgehog Signaling Network In Breast Cancermentioning
confidence: 99%
“…Gli1 (nuclear GLI1 protein) and ERα mRNA and protein expression correlate in many patient tumors and breast cancer cell lines [86,98100]. Estradiol treatment can induce GLI1 mRNA, and nuclear localization of GLI1 in ER positive breast cancer cell lines to promote proliferation, survival, and invasiveness [86,98,100]. On the other hand, a different study reported that Gli1 attenuated the mitogenic response of breast cancer cells to estradiol [92].…”
Section: Hedgehog Signaling Network In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations